2011
DOI: 10.5334/ijic.668
|View full text |Cite
|
Sign up to set email alerts
|

Ten years of integrated care for the older in France

Abstract: BackgroundThis paper analyzes progress made toward the integration of the French health care system for the older and chronically ill population.PoliciesOver the last 10 years, the French health care system has been principally influenced by two competing linkage models that failed to integrate social and health care services: local information and coordination centers, governed by the social field, and the gerontological health networks governed by the health field. In response to this fragmentation, Homes fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 13 publications
1
36
0
4
Order By: Relevance
“…Le développement des établissements d'HAD qui doit accompagner la transition épidémiologique sur le territoire français, nécessitent par ailleurs un changement dans les pratiques professionnelles avec une plus grande diffusion de la culture gériatrique et des interventions multidisciplinaires. Enfin, les établissements d'HAD doivent poursuivre le renforcement des partenariats sur leur territoire avec l'offre de services qui est souvent plé-thorique afin de réduire les fragmentations nombreuses de notre système de santé [8,9] et d'améliorer la qualité des interventions auprès de cette population âgée malade à domicile.…”
Section: Resultsunclassified
“…Le développement des établissements d'HAD qui doit accompagner la transition épidémiologique sur le territoire français, nécessitent par ailleurs un changement dans les pratiques professionnelles avec une plus grande diffusion de la culture gériatrique et des interventions multidisciplinaires. Enfin, les établissements d'HAD doivent poursuivre le renforcement des partenariats sur leur territoire avec l'offre de services qui est souvent plé-thorique afin de réduire les fragmentations nombreuses de notre système de santé [8,9] et d'améliorer la qualité des interventions auprès de cette population âgée malade à domicile.…”
Section: Resultsunclassified
“…Four of the articles related to adaptation and implementation in France [15, 16, 28, 29], and one study [30] reported on evidence from both France and Quebec. The 45 articles accessed for this review can be broadly assigned to four categories (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In France, since the 1960s, numerous public policies have been based on the idea of coordination [6, 7]. Basically, these systems were not intended to transform the missions of existing organisations, but rather their interconnectivity.…”
Section: How Does Integration Differ From Coordination?mentioning
confidence: 99%